(untitled) (ex æquo, 2023)
Gender issues in architecture: history(s), space(s) and professional and architectural experiences For many reasons, which also depend on the historical and social context in which they occur, in many occasions women have been excluded from the history or they have secondary roles. The architecture has supported its recognition in the life of the ‘great masters’ and their works, as ‘historic lighthouses’ able to legitimize almost all of a disciplinary discourse. So, once unraveled this male scenario, it includes both a brief history of architects (worldwide) and the phenomenon of the feminization of higher education in this subject. Concerning the profession, it is exposed which the current features of this, especially in Portugal, taking into account the unemployment, the conciliation of the work-family-personal-social levels, the concept of «career», the expectations and the management of time in the work-leisure binomial, using literature review as research methodology.